Basic Psychological Needs and its Relationship with Self-compassion among University Students - Ahmad M. Gazo; Ahmad M. Mahasneh; Feras Q. Al-Jobour (Islamic Guidance and Counseling Journal, 2023)
Background of the study: Basic psychological needs and self-compassion have gained significant attention in the field. Numerous studies have explored these concepts and their correlation with various personal variables due to their importance and their impact on positive personality aspects and mental health outcomes. Aims and scope of paper: This study aimed to investigate the relationship between basic psychological needs and self-compassion, as well as to examine potential differences in the level of basic psychological needs and self-compassion based on gender and college affliction. Methods: The study included a sample of 528 undergraduate students from Hashemite University. Data were collected using the Basic Psychological Needs Scale and Self-Compassion Scale. Result: The results indicated no gender-based differences in the level of basic psychological needs and two dimensions (competence and autonomy) due to gender, while males had higher level of relatedness compared females. Additionally, there were no significant differences in the level of basic psychological needs and two dimensions (competence and relatedness), between students' form scientific and humanities colleges. However, students from scientific colleges exhibited higher level of autonomy. The study also found that females had higher levels of self-compassion compared to males, with no differences based on college affiliation. Furthermore, positive correlations were observed between basic psychological needs and self-compassion, as well as and between psychological needs and self-compassion subscales (self-kindness, common humanity, and mindfulness). Conversely, a negative correlation was identified between basic psychological needs and self-compassion subscales (self-judgment, isolation, and over-identified). Conclusion: The basic psychological needs are of paramount importance in human development, and they serve as fundamental requirements throughout an individual's growth. The study revealed a positive correlation between basic psychological needs and self-compassion. These findings have valuable implications for the development of training and guidance programs aimed at enhancing basic psychological needs and self-compassion, which can ultimately contribute positively to the learning process.